2020
DOI: 10.1186/s13006-020-00262-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutritional status and child feeding practices: a retrospective study in Santal communities, Birbhum District, West Bengal, India

Abstract: Background: In West Bengal, according to the National Family Health Survey (NFHS-4) 2015-16, undernutrition and anemia are particularly common among scheduled tribe women and children. The purpose of this research is to assess the nutritional status of Adivasi mothers and child feeding patterns, relevant for clinical practice and the design of future preventive actions. These baseline characteristics were obtained in the scope of a feeding trial aimed at improving the hemoglobin concentration of the index chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…For fried and salty snack foods, the consumption in the same age groups was 34% and 66%, respectively. Similarly, among rural villages, the majority (79.3%) of 6–39-mo-olds consumed sweets, biscuits, cake, or sweet rice during the previous day ( 70 ). The consumption of SSBs was reported as 2.1% at 6–11 mo and 9.3% at 12–23 mo ( 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…For fried and salty snack foods, the consumption in the same age groups was 34% and 66%, respectively. Similarly, among rural villages, the majority (79.3%) of 6–39-mo-olds consumed sweets, biscuits, cake, or sweet rice during the previous day ( 70 ). The consumption of SSBs was reported as 2.1% at 6–11 mo and 9.3% at 12–23 mo ( 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…From 2011 to 2013, a cross-sectional study involving 1,090 females aged 20-60 years from nine major tribes: Santals, Oraons, and Koras in West Bengal; Santals, Bhumijs, and Bathudis in Odisha; and Dhodias, Kuknas, and Chaudharis in Gujarat found that, overall, 516 (47.4%) of the females were undernourished [ 11 ]. In 2015, a survey from 21 tribal villages in West Bengal documented that nearly half (49.4%) of the mothers were underweight, with a BMI of less than 18.5 kg/m 2 [ 16 ]. Over 40% of lactating mothers were undernourished using BMI criteria among the KOL tribe in Chitrakoot, Uttar Pradesh, in a cross-sectional study in 2021 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] However, the dietary iron intake was similar to the present study, the difference in the prevalence of anemia can be attributed to different study settings in the two studies. Higher anemia prevalence in Sahariya tribes,[ 23 ] Munda tribes,[ 24 ] and tribes from West Bengal[ 25 ] studies among women of the reproductive age group can be attributed to the lack of nutrition and healthcare access in low-performing states of India.…”
Section: Discussionmentioning
confidence: 99%